IMPLEMENTATION OF PERMENDIKDASMEN NUMBER 4 OF 2026 IN STRENGTHENING TEACHER PROFESSIONALISM IN CHARACTER DEVELOPMENT OF SENIOR HIGH SCHOOL - Raihana Hisan Taqiyyah; Siti Nurbayani; Siti Komariah (Universitas Labuhanbatu, 2026)
Purpose – This article examines the implementation of the Regulation of the Minister of Primary and Secondary Education (Permendikdasmen) Number 4 of 2026 concerning Protection for Educators and Education Personnel and its contribution to strengthening teacher professionalism in fostering the character of high school students, as well as developing a conceptual model that explains the causal mechanism between legal protection, psychological security, teacher professional agency, and character education.Methodology – The research used a qualitative approach with a case study design in one State High School, involving in-depth interviews with sixteen informants, participant observation, and document study. It analyzed the data thematically, with data validity strengthened through source triangulation and member checking.Findings – Legal certainty has been proven to form psychological security and self-efficacy of teachers that encourage the courage to uphold discipline, but this change in attitude only manifests into real action when supported by contextual resources in the form of principal's leadership and collegial solidarity; On the other hand, the gap in advocacy literacy and the residual concern about social-digital pressures show the structural limitations of legal instruments in reaching risks beyond the legal-formal realm.Contribution – This research fills the gap that has separated the study of teachers' legal protection from the theory of professionalism and character education, with the main contribution being the PELITA Model (Strengthening Regulatory Understanding, Continuous Education and Socialization, Structural Advocacy Services, Collegial Interaction, Transparency and Documentation, and Public Communication Adaptation), a cyclical framework that synthesizes the causal chain of legal protection–psychological safety–teacher agency–character education also offers practical guidance for other high school education units.